2015
DOI: 10.1007/s00508-015-0707-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, natural history, and predictors of mortality in patients with acute-on-chronic liver failure (ACLF)

Abstract: ACLF is a serious condition with high short-term mortality. Because ACLF is reversible, it is necessary to identify at-risk patients as soon as possible to treat acute events in a timely manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
5
15
2
Order By: Relevance
“…In our study, approximately a half of the patients had a lethal outcome and the 28-day mortality was 37.5%, indicating that ACLF patients have a very high short-term morality rate. Previous studies have also demonstrated that ACLF is a serious and challenging condition with a very high short-term mortality [2,[6][7][8][9] The mean age in our cohort was 60.1 ± 9.9, which is similar to the previous study of Mikolašević et al [7], but different from the study of Dhiman et al [18], where the mean age was 46 ± 13 years. We can explain the differences by the large number of patients with ALD, where the onset of the disease was usually at an older age.…”
Section: Prognostic Scoressupporting
confidence: 67%
See 2 more Smart Citations
“…In our study, approximately a half of the patients had a lethal outcome and the 28-day mortality was 37.5%, indicating that ACLF patients have a very high short-term morality rate. Previous studies have also demonstrated that ACLF is a serious and challenging condition with a very high short-term mortality [2,[6][7][8][9] The mean age in our cohort was 60.1 ± 9.9, which is similar to the previous study of Mikolašević et al [7], but different from the study of Dhiman et al [18], where the mean age was 46 ± 13 years. We can explain the differences by the large number of patients with ALD, where the onset of the disease was usually at an older age.…”
Section: Prognostic Scoressupporting
confidence: 67%
“…The joint American Association for the Study of Liver Disease and European Association for the Study of the Liver (AASLD/EASL) identifies ACLF as a syndrome with a high mortality rate, which includes the subgroup of cirrhotic patients who develop organ failure, with/without an identifiable precipitating event, such as variceal bleeding, acute alcoholism or infection [1,5]. Researchers from the EASL -Chronic Liver Failure Consortium (CLIF) prospectively studied patients with chronic liver disease (CLD) and AD, and found that patients with AD who had organ failure and high 28-day mortality rates, could be diagnosed with ACLF [1,2,6,7]. Due to a very high risk of mortality, ACLF patients require early identification and intensive treatment [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In different phase, patients undergo various pathophysiology [2]. In advanced phase, immune damage and hypoxic-ischemic damage may be dominant [3].…”
mentioning
confidence: 99%
“…Another observational study indicated that the presence of SIRS on admission was associated with in-hospital mortality in patients with acute-on-chronic liver failure (8). In cirrhotic patients, SIRS is associated with portal hypertension-related complications, poor hospital outcomes, and mortality.…”
mentioning
confidence: 99%